A method for preparing furfuryl alcohol resin-based porous carbon balls and furfuryl alcohol resin-based porous carbon balls
By adding pore-forming agent to furfuryl alcohol resin and carbonizing and activation, the problem of dense internal structure of porous carbon balls is solved, forming a large pore structure, and improving its performance in the fields of catalysis and adsorption separation.
Patent Information
- Application Number
- CN202111541308.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-12-16
AI Technical Summary
The internal structure of porous carbon balls prepared with furfuryl alcohol is compact, which limits the mass transfer process of molecules inside the carbon balls and affects their performance in catalysis and adsorption.
By adding a pore-forming agent to furfuryl alcohol and liquid furfuryl alcohol resin, condensing and curing in the presence of a dispersant and an acid catalyst, a composite ball of furfuryl alcohol resin and pore-forming agent is formed, and then carbonized and activated, the pore structure inside the carbon ball is adjusted.
The internal structure of furfurfurol resin-based porous carbon balls has been realized to become a "cheese-like" or "pomegranate-like" macroporous structure, which significantly improves its specific surface area and its application potential in the fields of catalytic and adsorption separation.
Smart Images

Figure HDA0003414387720000011 
Figure HDA0003414387720000012 
Figure HDA0003414387720000021
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a furfuryl alcohol resin-based porous carbon ball and a furfuryl alcohol resin-based porous carbon ball, and belongs to the field of porous carbon material preparation. Background Art
[0002] Porous carbon balls have the advantages of smooth surface, controllable particle size, and low fluid resistance. They are widely used in various fields such as adsorption, separation, and catalysis. According to the difference in raw materials, spherical activated carbon can be roughly divided into three categories: coal-based, asphalt-based, and polymer-based spherical porous carbon. Among them, the furfuryl alcohol resin-based porous carbon balls whose raw materials are derived from biomass are in line with the direction of low-carbon and environmentally friendly development and have broad prospects. For example, in Chinese patents CN102712743B and CN103443164B, water is used as the reaction medium, and the furfuryl alcohol condensation resin is granulated and solidified in the presence of a dispersant stabilizer and an acid catalyst to form spherical solidified resin particles, and then spherical carbon particles are obtained by carbonization and activation. However, in this process, the porous carbon balls prepared with furfuryl alcohol as the raw material have a "dense" structure inside, which is not conducive to the mass transfer process of molecules inside the porous carbon balls during adsorption and catalysis. Introducing a large pore structure inside the spherical activated carbon will greatly improve the mass transfer process of molecules inside the spherical activated carbon. Summary of the invention
[0003] According to one aspect of the present application, a method for preparing furfuryl alcohol resin-based porous carbon balls is provided. The method has a simple process and the internal pore structure of the carbon balls can be adjusted by adjusting the amount of pore-forming agent. The method has broad application prospects in the fields of catalysis and adsorption separation.
[0004] In one aspect of the present application, a method for preparing furfuryl alcohol resin-based porous carbon spheres is provided.
[0005] The preparation method comprises:
[0006] (1) mixing furfuryl alcohol and / or liquid furfuryl alcohol resin with a pore former in water to form a mixture,
[0007] (2) contacting the mixture with a dispersant and an acid catalyst, and condensing and curing the mixture to obtain composite balls of furfuryl alcohol resin and pore-forming agent;
[0008] (3) Carbonizing the composite balls of the furfuryl alcohol resin and the pore-forming agent to obtain the furfuryl alcohol resin-based porous carbon balls.
[0009] As a specific embodiment, the preparation method comprises:
[0010] (a) mixing furfuryl alcohol and / or liquid furfuryl alcohol resin with a pore former in a reaction medium of water;
[0011] (b) condensing and curing the furfuryl alcohol and / or liquid furfuryl alcohol resin in the presence of a dispersant and an acid catalyst to obtain composite balls of furfuryl alcohol resin and a pore-forming agent;
[0012] (c) The composite balls are carbonized or first carbonized and then activated to obtain furfuryl alcohol resin-based porous carbon balls.
[0013] Alternatively, the liquid furfuryl alcohol resin may be a liquid furfuryl alcohol resin pre-synthesized in the reaction medium water or commercially available.
[0014] Optionally, the pore-forming agent is a polymer compound that is insoluble in water but soluble in furfuryl alcohol and liquid furfuryl alcohol resin;
[0015] Optionally, the mass ratio of the pore-forming agent to furfuryl alcohol or liquid furfuryl alcohol resin is 0.05 to 1.0.
[0016] Optionally, the mass ratio of the pore former to furfuryl alcohol or liquid furfuryl alcohol resin is 0.1 to 0.5.
[0017] Optionally, the upper limit of the mass ratio of the pore former to furfuryl alcohol or liquid furfuryl alcohol resin can be independently selected from 0.2, 0.3, 0.4, 0.5; the lower limit can be independently selected from 0.1, 0.2, 0.3, 0.4;
[0018] Optionally, the dispersant is a colloid protective agent;
[0019] Optionally, the mass ratio of the colloidal protective agent to furfuryl alcohol or liquid furfuryl alcohol resin is 0.0001 to 0.5.
[0020] Optionally, the upper limit of the mass ratio of the colloidal protective agent to furfuryl alcohol or liquid furfuryl alcohol resin can be independently selected from 0.001, 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5; the lower limit can be independently selected from 0.0001, 0.001, 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4;
[0021] Optionally, the colloidal protective agent is selected from at least one of gum arabic, polyvinyl alcohol or carboxymethyl cellulose.
[0022] Optionally, the acid catalyst is selected from at least one of sulfuric acid, phosphoric acid, hydrochloric acid, nitric acid, benzenesulfonic acid, alkylbenzenesulfonic acid, oxalic acid, maleic anhydride, maleic acid, and citric acid;
[0023] Optionally, the mass ratio of the acid catalyst to furfuryl alcohol or liquid furfuryl alcohol resin is 0.0001 to 0.1.
[0024] Optionally, the upper limit of the mass ratio of the acid catalyst to furfuryl alcohol or liquid furfuryl alcohol resin can be independently selected from 0.002, 0.004, 0.01, 0.05, 0.1; the lower limit can be independently selected from 0.0001, 0.002, 0.004, 0.01, 0.05;
[0025] Optionally, the polymer compound is selected from at least one of polypropylene glycol and polybutylene glycol;
[0026] Optionally, the polymer compound has a weight average molecular weight of 800 to 5000.
[0027] Optionally, the condensation curing temperature is 60 to 100° C., and the time is 0.5 to 12 hours.
[0028] Optionally, the upper limit of the condensation curing temperature can be independently selected from 80°C, 85°C, 95°C, and 100°C; the lower limit can be independently selected from 60°C, 80°C, 85°C, and 95°C;
[0029] Optionally, the upper limit of the condensation curing time can be independently selected from 1 hour, 3 hours, 3.5 hours, 6 hours, 8 hours, 10 hours, and 12 hours; the lower limit can be independently selected from 0.5 hours, 1 hour, 3 hours, 3.5 hours, 6 hours, 8 hours, and 10 hours;
[0030] Optionally, the condensation curing is carried out in an inert atmosphere;
[0031] Optionally, the carbonization temperature is 600 to 1000° C., and the time is 0.5 to 12 hours.
[0032] Optionally, the upper limit of the carbonization temperature may be independently selected from 700°C, 800°C, 950°C, and 1000°C; the lower limit may be independently selected from 600°C, 700°C, 800°C, and 950°C;
[0033] Optionally, the upper limit of the carbonization time can be independently selected from 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours; the lower limit can be independently selected from 0.5 hours, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, and 10 hours;
[0034] Optionally, the carbonization further includes activation;
[0035] Optionally, the activation temperature is 800-1000° C., and the time is 0.5 to 12 hours.
[0036] Optionally, the upper limit of the activation temperature may be independently selected from 850°C, 900°C, and 1000°C; the lower limit may be independently selected from 800°C, 850°C, and 900°C;
[0037] Optionally, the upper limit of the activation time can be independently selected from 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours; the lower limit can be independently selected from 0.5 hours, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, and 10 hours.
[0038] Optionally, the activation is performed under the conditions of water and / or carbon dioxide.
[0039] In another aspect of the present application, a furfuryl alcohol resin-based porous carbon ball prepared by the above method is provided, wherein the furfuryl alcohol resin-based porous carbon ball has a specific surface area of 20 m 2 / g~2000m 2 / g;
[0040] The internal structure of the furfuryl alcohol resin-based porous carbon ball is at least one of a cheese-like macroporous structure and a pomegranate-like structure.
[0041] The beneficial effects of this application include:
[0042] In the present application, a compatible pore-forming agent is added during the polymerization of furfuryl alcohol, and with the assistance of a dispersant, the furfuryl alcohol is condensed by acid catalysis to obtain a composite ball of furfuryl alcohol resin and the pore-forming agent, and the composite ball is carbonized and activated to obtain furfuryl alcohol resin-based spherical activated carbon. The preparation method is simple in process, and the macroporous structure inside the carbon ball can be adjusted by adjusting the amount of the pore-forming agent, which has broad application prospects in the fields of catalysis and adsorption separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the SEM image of the porous carbon balls obtained in Example 1 of the present invention.
[0044] Figure 2 This is the SEM image of the porous carbon balls obtained in Example 2 of the present invention.
[0045] Figure 3 This is the SEM image of the porous carbon balls obtained in Example 3 of the present invention.
[0046] Figure 4 This is the SEM image of the porous carbon balls obtained in Example 4 of the present invention.
[0047] Figure 5 This is the SEM picture of the porous carbon balls obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0049] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0050] The measuring instruments used in the examples of the present application are as follows: the specific surface area of the porous carbon balls was tested on an ASAP 2460 physical adsorption instrument produced by McMeretic Corporation of the United States; the microstructure of the porous carbon balls was observed using a JSM-7800F field emission scanning electron microscope (SEM) produced by JEOL Ltd.
[0051] Example 1
[0052] 560g furfuryl alcohol, 140g polypropylene glycol 2000, 1.25g oxalic acid and 1000g water were stirred evenly, and prepolymerized in a water bath at 80°C for 3 hours. 100g water, 4.8g 5% aqueous solution of gum arabic and 14.2g 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 95°C, and kept at this temperature for 3.5 hours to cure the furfuryl alcohol resin beads. Cooled to room temperature, filtered, washed and dried to obtain furfuryl alcohol resin beads. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 0.5 hours to obtain furfuryl alcohol resin-based carbon balls. The obtained carbon balls were steam activated at 900°C for 8 hours to obtain spherical activated carbon.
[0053] The SEM images confirmed that the carbon balls were spherical with a good appearance and contained large pores with a "cheese-like" structure. Figure 1 The specific surface area measured by nitrogen physical adsorption is 1218m 2 / g.
[0054] Example 2
[0055] 490g furfuryl alcohol, 210g polypropylene glycol 2000, 1.31g oxalic acid and 1000g water were stirred evenly, and prepolymerized in a water bath at 80°C for 3 hours. 100g water, 2.2g 5% aqueous solution of gum arabic and 13.9g 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 95°C, and kept at this temperature for 4 hours to cure the furfuryl alcohol resin beads. Cooled to room temperature, filtered, washed and dried to obtain furfuryl alcohol resin beads. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 0.5 hours to obtain furfuryl alcohol resin-based carbon balls.
[0056] The SEM images confirmed that the carbon balls were spherical and well-surfaced, with a continuous smooth shell on the outside and uniform micron-sized particles on the inside similar to a "pomegranate-like" structure. Figure 2 The specific surface area measured by nitrogen physical adsorption is 237m 2 / g.
[0057] Example 3
[0058] 525g furfuryl alcohol, 175g polypropylene glycol 2000, 1.31g oxalic acid and 1000g water were stirred evenly, and prepolymerized in a water bath at 80°C for 3 hours. 100g water, 4.8g 5% aqueous solution of gum arabic and 13.9g 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 95°C, and kept at this temperature for 3.5 hours to cure the furfuryl alcohol resin beads. Cooled to room temperature, filtered, washed and dried to obtain furfuryl alcohol resin beads. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 0.5 hours to obtain furfuryl alcohol resin-based carbon beads.
[0059] The SEM images confirmed that the carbon ball was spherical with a good appearance and a composite structure of "cheese-like" and "pomegranate-like" inside. Figure 3 .
[0060] Example 4
[0061] 75g of furfuryl alcohol, 75g of polypropylene glycol 2000, 0.33g of maleic anhydride and 250g of water were stirred evenly, and prepolymerized in a water bath at 80°C for 3 hours. 50g of water, 1.48g of 5% aqueous solution of polyvinyl alcohol and 4.58g of 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 95°C, and kept at this temperature for 3 hours to cure the furfuryl alcohol resin beads. Cooled to room temperature, filtered, washed and dried to obtain furfuryl alcohol resin beads. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 0.5 hours to obtain furfuryl alcohol resin-based carbon beads.
[0062] The SEM images confirmed that the carbon ball was spherical with a good appearance and a pomegranate-like composite structure inside. Figure 4 .
[0063] Example 5
[0064] 560g of furfuryl alcohol, 100g of polypropylene glycol 2000, 1.25g of oxalic acid and 1000g of water were stirred evenly, and prepolymerized in a water bath at 80°C for 3 hours. 100g of water, 7.0g of 5% aqueous solution of gum arabic and 14.2g of 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 98°C, and kept at this temperature for 2 hours to cure the furfuryl alcohol resin beads. Cool to room temperature, filter, wash and dry to obtain furfuryl alcohol resin beads. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 6 hours to obtain furfuryl alcohol resin-based carbon balls. The carbon balls were steam activated at 900°C for 8 hours to obtain spherical activated carbon. The specific surface area measured by nitrogen physical adsorption was 1336m 2 / g.
[0065] Example 6
[0066] 560g of furfuryl alcohol, 56g of polypropylene glycol 2000, 1.25g of oxalic acid and 1000g of water were stirred evenly, and prepolymerized in a water bath at 80°C for 1 hour. 100g of water, 7.0g of 5% aqueous solution of gum arabic and 14.2g of 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 95°C, and kept at this temperature for 5 hours to cure the furfuryl alcohol resin beads. After cooling to room temperature, the furfuryl alcohol resin beads were obtained after filtration, washing and drying. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 3 hours to obtain furfuryl alcohol resin-based carbon balls. The carbon balls were steam activated at 850°C for 8 hours to obtain spherical activated carbon. The specific surface area measured by nitrogen physical adsorption was 902m 2 / g.
[0067] Example 7
[0068] Stir 560g of furfuryl alcohol, 140g of polypropylene glycol 1000, 1.25g of oxalic acid and 1000g of water. Add 100g of water, 4.8g of 5% aqueous solution of gum arabic and 14.2g of 10% aqueous solution of dodecylbenzene sulfonic acid to the prepolymerized furfuryl alcohol resin prepared above, stir evenly, heat to 95°C, and keep the temperature constant for 3 hours to cure the furfuryl alcohol resin beads. Cool to room temperature, filter, wash and dry to obtain furfuryl alcohol resin beads. Place the furfuryl alcohol resin beads in a rotary tubular furnace, heat and cure under a nitrogen atmosphere, and maintain the temperature at 800°C for 8 hours to complete carbonization to obtain furfuryl alcohol resin-based carbon balls. The carbon balls are steam activated at 850°C for 4 hours to obtain spherical activated carbon. The specific surface area measured by nitrogen physical adsorption is 602m 2 / g.
[0069] Example 8
[0070] 560g of furfuryl alcohol, 120g of polypropylene glycol 4000, 1.25g of maleic anhydride and 800g of water were stirred evenly, and prepolymerized in a water bath at 60°C for 6 hours. 50g of water, 4.6g of 5% aqueous solution of gum arabic and 11g of 10% aqueous solution of p-toluenesulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 80°C, and kept at this temperature for 9 hours to cure the furfuryl alcohol resin beads. After cooling to room temperature, the furfuryl alcohol resin beads were obtained after filtration, washing and drying. The furfuryl alcohol resin beads were placed in a rotary tubular furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 2 hours to obtain furfuryl alcohol resin-based carbon beads. The carbon beads were activated with carbon dioxide at 950°C for 8 hours to obtain spherical activated carbon. The specific surface area measured by nitrogen physical adsorption was 1173m 2 / g.
[0071] Example 9
[0072] 560g of furfuryl alcohol, 140g of polybutylene glycol 2000, 1.50g of maleic acid and 1000g of water were stirred evenly. 150g of water, 4.6g of 2% aqueous solution of carboxymethyl cellulose and 7g of 5% aqueous solution of sulfuric acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 85°C, and kept at this temperature for 3.5 hours to cure the furfuryl alcohol resin beads. Cooled to room temperature, filtered, washed and dried to obtain furfuryl alcohol resin beads. The furfuryl alcohol resin beads were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 0.5 hours to obtain furfuryl alcohol resin-based carbon balls. The carbon balls were activated with carbon dioxide at 950°C for 8 hours to obtain spherical activated carbon. The specific surface area measured by nitrogen physical adsorption was 1319m 2 / g.
[0073] Example 10
[0074] Mix 560g of furfuryl alcohol, 140g of polybutylene glycol 4000, 1.50g of citric acid and 1000g of water. Add 150g of water, 4.6g of 2% aqueous solution of carboxymethyl cellulose and 7g of 5% aqueous solution of hydrochloric acid to the prepolymerized furfuryl alcohol resin prepared above, stir evenly, heat to 85°C, and keep the temperature constant for 3.5 hours to cure the furfuryl alcohol resin beads. Cool to room temperature, filter, wash and dry to obtain furfuryl alcohol resin beads. Place the furfuryl alcohol resin beads in a rotary tube furnace, heat and cure under a nitrogen atmosphere, and maintain the temperature at 800°C for 4 hours to complete carbonization to obtain furfuryl alcohol resin-based carbon balls. The carbon balls are water activated at 880°C for 8 hours to obtain spherical activated carbon. The specific surface area measured by nitrogen physical adsorption is 1134m 2 / g.
[0075] Comparative Example 1
[0076] 560g furfuryl alcohol, 1.20g oxalic acid and 1000g water were stirred and dissolved, and prepolymerized in a water bath at 80°C for 3 hours. 100g water, 4.7g 5% aqueous solution of gum arabic and 14.1g 10% aqueous solution of dodecylbenzene sulfonic acid were added to the prepolymerized furfuryl alcohol resin prepared above, stirred evenly, heated to 95°C, and kept at this temperature for 3h to cure the furfuryl alcohol resin balls. Cooled to room temperature, filtered, washed and dried to obtain furfuryl alcohol resin balls. The furfuryl alcohol resin balls were placed in a rotary tube furnace, heated and cured under a nitrogen atmosphere, and carbonized at 800°C for 0.5 hours to obtain furfuryl alcohol resin-based carbon balls.
[0077] The SEM images confirmed that the obtained resin particles were spherical and had a continuous dense structure inside. Figure 5 The specific surface area measured by nitrogen physical adsorption is 20m 2 / g, which is much lower than the result in Example 3.
[0078] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing furfuryl alcohol resin-based porous carbon balls, characterized in that: The preparation method comprises: (1) mixing furfuryl alcohol and / or liquid furfuryl alcohol resin with a pore former in water to form a mixture; (2) contacting the mixture with a dispersant and an acid catalyst, and condensing and curing the mixture to obtain composite balls of furfuryl alcohol resin and pore-forming agent; (3) carbonizing the composite balls of the furfuryl alcohol resin and the pore-forming agent to obtain the furfuryl alcohol resin-based porous carbon balls; The pore-forming agent is a high molecular compound that is insoluble in water but soluble in furfuryl alcohol and liquid furfuryl alcohol resin; The polymer compound is selected from at least one of polypropylene glycol and polybutylene glycol; The polymer compound has a weight average molecular weight of 800 to 5000; The dispersant is a colloid protective agent; The colloid protective agent is selected from at least one of gum arabic, polyvinyl alcohol or carboxymethyl cellulose.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the pore former to furfuryl alcohol or liquid furfuryl alcohol resin is 0.05-1.
0.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the pore former to furfuryl alcohol or liquid furfuryl alcohol resin is 0.1-0.
5.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the colloid protective agent to furfuryl alcohol or liquid furfuryl alcohol resin is 0.0001-0.
5.
5. The preparation method according to claim 1, characterized in that: The acid catalyst is selected from at least one of sulfuric acid, phosphoric acid, hydrochloric acid, nitric acid, benzenesulfonic acid, alkylbenzenesulfonic acid, oxalic acid, maleic anhydride, maleic acid, and citric acid; The mass ratio of the acid catalyst to furfuryl alcohol or liquid furfuryl alcohol resin is 0.0001-0.
1.
6. The preparation method according to claim 1, characterized in that: The condensation curing temperature is 60-100°C and the time is 0.5-12 hours; The condensation curing is carried out in an inert atmosphere.
7. The preparation method according to claim 1, characterized in that: The carbonization temperature is 600-1000° C., and the time is 0.5-12 hours.
8. The preparation method according to claim 1, characterized in that: The carbonization further includes activation; The activation temperature is 800-1000°C and the time is 0.5 to 12 hours; The activation is carried out under the conditions of water and / or carbon dioxide.
Citation Information
Patent Citations
A method for manufacturing spherical furfuryl alcohol resin particles, spherical furfuryl alcohol resin particles obtained by the method, and spherical carbon particles and spherical activated carbon particles obtained using the method.
CN102712743B
A method for manufacturing spherical furfuryl alcohol resin particles, and the spherical furfuryl alcohol resin particles, spherical carbon particles, and spherical activated carbon particles obtained by the method.
CN103443164B
Method for producing spherical furfuryl alcohol resin particles, spherical furfuryl alcohol resin particles produced thereby, spherical carbon particles and spherical activated carbon particles
CN103443164A